2010
DOI: 10.1002/jbm.b.31615
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoparticles enhanced antibacterial activity of ciprofloxacin against Staphylococcus aureus and Escherichia coli

Abstract: Nanoparticle metal oxides offer a wide variety of potential applications in medicine due to the unprecedented advances in nanobiotechnology research. In this work, the effect of zinc oxide (ZnO) nanoparticles prepared by mechano-chemical method on the antibacterial activity of different antibiotics was evaluated using disk diffusion method against Staphylococcus aureus and Escherichia coli. The average size of ZnO nanoparticles was between 20 nm and 45 nm. Although ZnO nanoparticles (500 microg/disk) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(136 citation statements)
references
References 45 publications
8
122
1
Order By: Relevance
“…Furthermore, nanoparticles tagged with antibiotics have been shown to increase the concentration of the antibiotics at the site of bacterium-antibiotic interaction, and facilitate in the binding of antibiotics to microorganisms (Allahverdiyev et al 2011). Our results are in terms with the study conducted by Banoee et al (2010) showing better activity of ciprofloxacin nanoparticle combination as compared to ampicillin nanoparticle combination. They reported 27 and 22% increase in inhibition zone areas was observed against S. aureus and E. coli, respectively when ZnO nanoparticles combine with ciprofloxacin.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, nanoparticles tagged with antibiotics have been shown to increase the concentration of the antibiotics at the site of bacterium-antibiotic interaction, and facilitate in the binding of antibiotics to microorganisms (Allahverdiyev et al 2011). Our results are in terms with the study conducted by Banoee et al (2010) showing better activity of ciprofloxacin nanoparticle combination as compared to ampicillin nanoparticle combination. They reported 27 and 22% increase in inhibition zone areas was observed against S. aureus and E. coli, respectively when ZnO nanoparticles combine with ciprofloxacin.…”
Section: Discussionsupporting
confidence: 83%
“…This is done by the presence of fluore group and carboxyl group on the ciprofloxacin. The fluore group interacts with the chelating Zn atom stabilizing the ciprofloxacinnanoparticle combination whereas carboxyl group serves as an obvious target for chelation by metal ions (Banoee et al 2010). Moreover, presence of doping ion on ZnO nanoparticle surface accelerates generation of reactive oxygen species (rOS) due to coupling or synergistic effects of Mn, Co, Cu and Fe loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many organic and inorganic compounds have been reported to enhance the antibacterial activity of different antibiotics against many bacteria and fungi resistant test strains [14]. Metallic ions and metallic nanoparticles including zinc and silver have particularly shown promise when used in combination with a number of antibiotics such as ciprofloxacin [15], penicillin G, amoxicillin, erythromycin, clindamycin, vancomycin [16], ampicillin, kanamycin, erythromycin and chloramphenicol [17] in different Gram positive or Gram negative test strains. In a recent approach, Rai et al reported the antibiotic mediated synthesis of Au NPs with potent antimicrobial activity for application in antimicrobial coatings [18].…”
Section: Introductionmentioning
confidence: 99%
“…Sections were deparaffinized in xylene and subsequently stained with Haematoxylin and Eosin (H and E) for light microscopy. 30 …”
Section: Histopathological Assessmentmentioning
confidence: 99%